2015
DOI: 10.1155/2015/805328
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Comparative Study of 26 Biochemical Markers in Seminal Plasma and Serum in Infertile Men

Abstract: Introduction. The relationships of the biochemical components in seminal plasma and serum, and their origins and physiological effects in male reproductive system have been poorly understood. Methods. Based on the calibration and quality control measures, 26 biochemical markers, in seminal plasma and serum samples from 36 male infertility patients with nonazoospermia were detected and compared. Results. Only PA was undetectable in all seminal plasma samples. There were significant differences of all other 24 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
1
19
0
2
Order By: Relevance
“…However, no significant difference in semen and serum glutathione level was found between the different groups. These results agree with previous reports by Guz et al [33] and Feng et al [34]; they reported no significant differences in semen and serum uric acid concentration between fertile and infertile men [33,34]. However, in a disagreement, Bhardwaj et al [35] reported a significant decrease in semen glutathione level in infertile men, and Thiele et al [14] reported significant decrease in uric acid concentration in normozoospermic infertile men comparing to fertile men.…”
Section: Discussionsupporting
confidence: 91%
“…However, no significant difference in semen and serum glutathione level was found between the different groups. These results agree with previous reports by Guz et al [33] and Feng et al [34]; they reported no significant differences in semen and serum uric acid concentration between fertile and infertile men [33,34]. However, in a disagreement, Bhardwaj et al [35] reported a significant decrease in semen glutathione level in infertile men, and Thiele et al [14] reported significant decrease in uric acid concentration in normozoospermic infertile men comparing to fertile men.…”
Section: Discussionsupporting
confidence: 91%
“…Seminal plasma is the protein-rich fluid part of the semen and it plays an important role in sperm metabolism as well as sperm function. The analyses of seminal enzyme activities and the concentrations of biochemical elements have been performed in men and animals [1][2][3][4] in order to establish the functions of the different components, because some of them are still obscure.…”
Section: Introductionmentioning
confidence: 99%
“…La diminution du nombre de spermatozoïdes a trois principales causes. Les causes pré-testiculaires qui sont liées aux niveaux hormonaux sécrétés par l'hypophyse (Gordetsky et al, 2011). Les causes testiculaires qui sont liées à des lésions telles qu'une varicocèle (El Bardisi, 2018) et les causes post-testiculaires liées à une obstruction ou absence congénital des conduits déférents Ho et al (2015).…”
Section: Discussionunclassified
“…En effet, la composante masculine dans l'infertilité du couple a été estimée en Afrique subsaharienne à 20-40% . Pour ces hommes qui acceptent de consulter pour infertilité, en dehors du bilan hormonal, il est préconisé la réalisation d'une analyse de sperme, sous forme de spermogramme et spermocytogramme (Cooper et al, 2010 ;Esteves et al, 2012). Par ailleurs, une analyse biochimique du sperme peut également contribuer dans l'exploration de l'infertilité masculine (Feng et al, 2015).…”
Section: Introductionunclassified